Solve for z
z = -\frac{13}{2} = -6\frac{1}{2} = -6.5
Share
Copied to clipboard
8z-5=10z+8
Combine 20z and -12z to get 8z.
8z-5-10z=8
Subtract 10z from both sides.
-2z-5=8
Combine 8z and -10z to get -2z.
-2z=8+5
Add 5 to both sides.
-2z=13
Add 8 and 5 to get 13.
z=\frac{13}{-2}
Divide both sides by -2.
z=-\frac{13}{2}
Fraction \frac{13}{-2} can be rewritten as -\frac{13}{2} by extracting the negative sign.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}